Discriminating dose, cypermethrin, indoxacarb, methomyl, spinosad, quinalphos, resistance ratio - Salunke, P B; Lande, S S; Lande, G K (Indian Journal of Plant Protection, 2020)
Present investigations were carried out at Toxicology laboratory, Department of Entomology, Post Graduate Institute, Dr Panjabrao Deshmukh Krishi Vidyapeeth, Akola during the year 2013-14 to evaluate level of insecticide resistance in pigeonpea pod borer, Helicoverpa armigera (Hubner) collected from major pigeonpea growing districts of Vidarbha viz., Akola, Amaravati, Buldhana, Yavatmal and Washim to technical grade insecticides. Discriminating doses (LD99) of different insecticides was assessed for H. armigera population. LD99 value of cypermethrin for F1 and F6 population was 0.020010 Î¼g/larva and 0.001229 Î¼g/larva, respectively. LD99 value of quinalphos for F1 and F6 population was 0.023297 Î¼g/larva and 0.000866 Î¼g/larva, respectively. LD99 value of methomyl for F1 and F6 population was 0.036494 Î¼g/larva and 0.001273 Î¼g/larva, respectively. LD99 value of indoxacarb for F1 and F6 population was 0.038428 Î¼g/larva and 0.001172 Î¼g/larva, respectively. LD99 value of spinosad for F1 and F6 population was 0.103200 Î¼g/larva and 0.010196 Î¼g/larva, respectively